The Myth of the “Smoking Indian” - Alessandro Tarsia (Iperstoria)
This article examines the complex interplay between colonial exploitation and Indigenous resilience through the lens of tobacco species in the Pacific Northwest contact zone (1770s-1820s). Analyzing Eurocentric narratives and Indigenous responses, it critiques colonial ideologies that framed Indigenous tobacco practices as “primitive” while ignoring ancestral permaculture and spiritual traditions. Influenced by Orientalist and Eurocentric hierarchies, European explorers and fur traders dismissed native tobacco species like Nicotiana quadrivalvis and attenuata as inferior to industrially bred varieties, weaponizing addictive colonial tobacco to manipulate trade and foster dependency. However, Indigenous communities – including the Haida, Interior Salish, and Coast Salish – negotiated, adapted, or resisted these impositions. While some integrated colonial tobacco into “moditional” practices, blending traditional and introduced elements, others upheld prohibitions or repurposed the plant within spiritual and medicinal frameworks. The article highlights how colonial accounts, shaped by exploitative agendas, obscured Indigenous agency, permacultural knowledge, and pre-existing intertribal trade networks. Simultaneously, it reveals Indigenous resilience through oral histories and ethnobotanical evidence, challenging settler narratives that conflated cultural adaptation with assimilation. By interrogating sources from fur traders, missionaries, and Indigenous Knowledge Givers, the study exposes the enduring legacy of colonial tobacco in reshaping power dynamics, ecological practices, and cross-cultural perceptions. Ultimately, it argues that the “myth of the Smoking Indian” emerged from a deliberate colonial erasure of Indigenous sovereignty over tobacco, reinforcing white supremacist ideologies even as Indigenous communities asserted autonomy over their botanical traditions. This research reframes the contact zone as a contested space where tobacco became both a tool of colonial coercion and a medium for Indigenous survivance.